2015
DOI: 10.1371/journal.pone.0128341
|View full text |Cite
|
Sign up to set email alerts
|

Septic Shock in Advanced Age: Transcriptome Analysis Reveals Altered Molecular Signatures in Neutrophil Granulocytes

Abstract: Sepsis is one of the highest causes of mortality in hospitalized people and a common complication in both surgical and clinical patients admitted to hospital for non-infectious reasons. Sepsis is especially common in older people and its incidence is likely to increase substantially as a population ages. Despite its increased prevalence and mortality in older people, immune responses in the elderly during septic shock appear similar to that in younger patients. The purpose of this study was to conduct a genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 91 publications
2
22
0
Order By: Relevance
“…However, exposing neutrophils from young adults to pooled plasma from older patients with CAP and sepsis replicates the functional deficits seen in sepsis,33 which suggests that the CAP environment can alter cellular function. In keeping with this, murine models of sepsis in older mice show transcriptomic changes in neutrophils which would contribute to cellular dysfunction, implicating cellular energetics and epigenetics 68…”
Section: Host Immune System At the Extremes Of Agementioning
confidence: 67%
“…However, exposing neutrophils from young adults to pooled plasma from older patients with CAP and sepsis replicates the functional deficits seen in sepsis,33 which suggests that the CAP environment can alter cellular function. In keeping with this, murine models of sepsis in older mice show transcriptomic changes in neutrophils which would contribute to cellular dysfunction, implicating cellular energetics and epigenetics 68…”
Section: Host Immune System At the Extremes Of Agementioning
confidence: 67%
“…Studies of sepsis have shown an exponential increase in the population-based incidence of sepsis with age, followed closely by an increased mortality. In a small study of septic shock in advanced age, major molecular pathways were found to be deregulated following severe infection, indicating that the systemic inflammatory response differs according to age [15].…”
Section: Mortalitymentioning
confidence: 99%
“…Recently, it has also been shown that diminished expression levels of Atg5 contributed to reduced capacity of neutrophils to form NETs upon TLR2 ligand stimulation in aged mice, suggesting an important role of autophagy in maintaining the mechanism of NETs ( Xu et al, 2017 ). Interesting, in vitro NET generation is impaired in older adults in response to LPS and IL-8 ( Hazeldine et al, 2014 ), and reduced ATG5 gene expression ( Vieira da Silva Pellegrina et al, 2015 ; Xu et al, 2017 ). Consistent with this, inhibition of autophagy by pharmacological inhibitors or by small interfering RNA against ATG7 attenuated LC3 autophagy formation and significantly decreased NET generation in promyelocytes ( Ma et al, 2016 ).…”
Section: Autophagy and Net Formationmentioning
confidence: 99%